PENGARUH INFLASI DAN NILAI TUKAR RUPIAH TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI (PPN) PERIODE 2017-2021 - John Henry Wijaya; Nijar Muhamad Asy’ari (Jurnal Computech & Bisnis (e-Journal), 2022)
This study aims to determine whether inflation and the rupiah exchange rate affect the value added tax (VAT) revenue in the 2017-2021 period. The factors tested in this study are inflation and the rupiah exchange rate as independent variables, while value added tax (VAT) revenue as the dependent variable. The research method used in this study is the verification method. The population in this study is data on inflation reports, rupiah exchange rates, and reports on value added tax (VAT) receipts. The sampling technique used in this study is non-probability sampling with purposive sampling method, so that the samples in this study are data on inflation reports, rupiah exchange rates, and monthly value added tax (VAT) receipts published in the 2017-2021 period. Analysis of the data used in this study is multiple regression analysis using SPSS 25.00. The results of the research partially and simultaneously show that inflation and the rupiah exchange rate affect the value added tax (VAT) revenue. In addition, the magnitude of the influence of inflation and the rupiah exchange rate in contributing to the value added tax (VAT) revenue is 43.7%. Keywords : Inflation, Rupiah Exchange Rate, and Value Added Tax (VAT) Revenue